INFLUENCE OF TURMERIC POWDER (CURCUMA LONGA) ON EGG YOLK CHOLESTEROL AND TOTAL SERUM CHOLESTEROL IN RHODO WHITE LAYERS - A. Bharathidhasan; A. Subramanian; S. Ezhilvalavan; T.R. Pugazhenthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Turmeric powder (Curcuma longa) has been used in several countries as a traditional remedy for the treatment of many diseases. It is an established fact that the active principle present in the turmeric powder viz. curcumin has broad spectrum biological activities including antioxidant, anticancer, anti-inflammatory and lowering effects of lipid and cholesterol. Hence an experiment was conducted to study the influence of turmeric powder on egg yolk cholesterol and total serum cholesterol level of Rhodo White layers. Seventy two Rhodo White layers were randomly divided into four treatment groups where in turmeric powder was included in their ration @ 0, 0.05 %, 0.10 % and 0.15 %. Each treatment had three replicate of six birds each and reared with iso-nitrogenous and iso- calorie diet for a total period of 14 weeks from 26th week to 39th week of age. The birds were housed in cage system of rearing and they were fed with weighed quantities of feed with ad libitum water following uniform standard managemental practices. The egg yolk cholesterol and total serum cholesterol were estimated during 32 and 39th week of age. At 32 weeks of age, the egg yolk cholesterol level was significantly (P<0.01) reduced in all turmeric supplemented groups than control group. The maximum reduction of egg yolk cholesterol level by 32.9 % was observed in 0.15 % turmeric powder supplemented group when compared to control. The egg yolk cholesterol level was also found to be significantly (P<0.01) decreased at 39th week in all turmeric supplemented groups. The reduction of egg yolk cholesterol was by 19.42, 23.26 and 31.53 % in 0.05, 0.10 and 0.15 % respectively in turmeric supplemented groups compared to control. The total serum cholesterol level was also significantly (P<0.01) decreased at 32nd week and 39th week in turmeric powder supplemented group than control. The maximum decrease in total serum cholesterol was observed by 15.32% at 32 week and 17.20 % at 39 week in 0.15 % turmeric powder supplemented group than control. It was concluded that the inclusion of turmeric powder (Curcuma longa) at 0.15 % reduce the egg yolk cholesterol and total serum cholesterol in Rhodo White layers to the maximum extent.